Pain Management in Clinical and Health Psychology - Gianluca Castelnuovo (Frontiers Research Topics, 2018)
Chronic pain is a relevant health problem frequently associated with psychological distress, dysfunctions in physical and social functioning, reductions in quality of life and elevated direct and indirect costs. Medical approach is typically useful for treating chronic pain, but also psychological contributions play an important role in pain management. In fact psychological treatments are recognized as generally effective for pain. Psychological approaches in managing pain have evolved considerably and now understanding and managing the cognitions, emotions and behaviors that accompany the situation of discomfort can actually reduce the pain intensity and the interference of pain with daily life. Psychological therapies are highly indicated both for the treatment of painful conditions and for the treatment of pain related to several neurological diseases. The reviews and meta-analyses conducted to evaluate the effectiveness of different forms of psychotherapy across several disorders, although with different levels of experimental evidence, confirmed that psychological interventions can improve the experience of patients at every age (children, adolescents, adults, seniors). Similar positive results about psychotherapy efficacy were reported in specific pain disorders such as low back pain, fibromyalgia, tension-type headache and migraine, pain associated with rheumatoid arthritis, chronic abdominal pain in adolescents, chronic orofacial pain, etc. Clinical health psychology focuses also on the study of the psychological determinants in pain patients such as the role of depression, anxiety, pain-related disability, catastrophic thinking, psychological inflexibility, coping skills, beliefs, attitudes, expectations, self-efficacy, placebo and nocebo effects, etc. Different psychological models of pain and disability (such as Fear-avoidance, Acceptance and commitment, Misdirected problem solving, Self-efficacy and Stress-diathesis models) have tried to highlight the psychological processes behind pain. The major objective of the present Research Topic is to collect new scientific evidence, clinical experiences, reviews and opinion articles about clinical health psychology and psychotherapy in pain management and treatment. Moreover this RT will focus on psychological factors, basic psychological processes and theoretical models that could have an impact in the development of persistent pain and disability and implications for different therapies, considering psychological interventions in peri-operative pain and/or preventive interventions in sub-acute pain too.